SCIENCE AND ACCOUNTING. - Nelson, Edward G. (The Accounting Review, 1949)
The Article traces the origin and development of accounting as a science. In the United States during the first quarter of the twentieth century, accounting was a young and rapidly growing profession struggling to improve its adaptive behavior in an environment of mechanistic science. Accountants appealed to science for authority and found employment in a search for principles that would place accounting on a high plane of orthodoxy in an economic world arranged by a natural order of things. William Morse Cole defined his subject as "scientific analysis and record of business transactions,". In 1910 a LaSalle Extension University publication reported that "accounting is a science which aims at systematic presentation of business facts and whose rules are designed to indicate or state the principles upon which such a record of business facts must be made." The bright days of the golden 1920's found accounting with definite direction toward an acceptable goal. Hat- field wrote of the "science of accounting" in a formative stage, and warned against the foolhardiness of attempting categorical treatment of the subject. Science requires an instinctive faith in an "order of things." Is it not to be expected that many modern accountants, living in a scientific age, would search for authority with a faith in "nature," and with a desire to subdue the discipline with "irreducible and stubborn facts"?